METHODOLOGY FOR DEVELOPING THE EDUCATIONAL COMPETENCE OF FUTURE TEACHERS BASED ON PROJECT TECHNOLOGY - Kulmatova Khurshida Abdurakhmonovna (International Journal of Literature and Language Studies, 2026)
This article highlights the theoretical and practical foundations of a methodology for developing the educational competence of future teachers based on project technology. In the context of the ongoing modernization of the education system, alongside professional training, the formation of future teachers’ competence in effectively organizing educational activities has become increasingly important. The study analyzes the pedagogical potential of project technology, the structural components of educational competence, and methodological approaches that contribute to its development. Furthermore, the effectiveness of project technology is substantiated through examples of educational projects implemented with students majoring in pedagogy. The findings demonstrate that a project-based educational process contributes to the development of future teachers’ skills in planning, organizing, managing, and evaluating educational activities. The proposed methodology is characterized as an effective tool for ensuring the professional and personal development of future teachers, enhancing their readiness for innovative activities, and improving their educational competence.